Multi-resolution search with active shape models - Lanitis, Andreas; Cootes, Timothy F.; Taylor, Chris J. (My University, 1994)
We describe a multiresolution approach to image search using flexible shape models. This is an extension of work on active shape models (ASMs)-statistical models which iteratively deform to match image data. An ASM consists of a shape model controlling a set of landmark points, together with a statistical model of the grey-levels expected around each landmark. Both the shape model and the grey-level models are trained on sets of labelled example images. In order to apply a coarse-to-fine search strategy it is necessary to train a set of grey-level models for each landmark, one for every level of a multiresolution image pyramid. We demonstrate the approach and give results of quantitative experiments which show a significant increase in both speed, robustness and quality of fit compared to previous methods.
Keywords: Active shape model; Image resolution; Shape control; Pixel; Biomedical imaging; Biophysics; Deformable models; Statistics; Image converters; Iterative methods